The role of tin and iron in the production of Spanish copper red glass from the 19th to the 20th century - Mingyue Yuan; Jordi Bonet; Hiram Castillo-Michel; Marine Cotte; Nadine Schibille; Bernard Gratuze; Trinitat Pradell (Boletín de la Sociedad Española de Cerámica y Vidrio, 2024)
Little is known about the materials used in the manufacture of red window glass in the 19th and the first decade of the 20th century. Here, we have studied fragments from eight Spanish glasses from the 19th and 20th centuries. The red glasses consist of a single layer of red glass on a colourless glass substrate. The chemical composition, oxidation state, nature of colourants and crystalline precipitates were determined by a selection of microanalytical techniques. In the study, we have found that the red colour of the glass is due to the presence of Cu0 nanoparticles, the red glass layer has lower calcium content than the substrate glasses, which we found favours copper being present in the glass predominantly in Cu+. They also contain tin and iron while lead, described in historical and modern documentation, was absent. Tin must have been added to the glass as a Sn2+ compound and acted as a reducing agent for copper. Iron is also a well-known reducing agent, but does not act as such in the red glasses studied here. However, it may have facilitated the reduction of copper to Cu0 by promoting its incorporation into the glass as Cu+ rather than Cu2+. Resumen: Poco se sabe sobre los materiales utilizados en la fabricación de vidrios rojos planos en el siglo xix y primera década del xx, por ello se han estudiado ocho fragmentos españoles de la época. Todos ellos están formados por una sola capa de vidrio rojo sobre un sustrato de vidrio incoloro. La composición química, el estado de oxidación, la naturaleza de los colorantes y los precipitados cristalinos se han determinado mediante una selección de técnicas microanalíticas. Hemos encontrado que la capa de vidrio rojo contiene nanopartículas de Cu0, y que tiene un menor contenido de calcio menor que el vidrio sustrato, lo cual favorece que el cobre esté en el vidrio predominantemente como Cu+. Tal y como está descrito en la documentación histórica y moderna contienen estaño y hierro, pero no se ha verificado la presencia de plomo. El estaño se agregó al vidrio como un compuesto Sn2+ y actuó como agente reductor del cobre. El hierro a pesar de ser un agente reductor, no actúa como tal en los vidrios rojos estudiados. Sin embargo, su presencia podría facilitar la reducción del cobre a Cu0 al promover su incorporación al vidrio como Cu+ en lugar de Cu2+.